Uranium XAFS analysis of kidney from rats exposed to uranium. (20th February 2017) - Kitahara, Keisuke; Numako, Chiya; Terada, Yasuko; Nitta, Kiyohumi; Shimada, Yoshiya; Homma-Takeda, Shino
Abstract : Characterization of uranium accumulated in the micro‐regions of renal tubules of rats exposed to uranyl acetate was examined by micro‐X‐ray absorption fine‐structure analysis and the results showed the possible biotransformation of uranium in this in vivo system. Abstract : The kidney is the critical target of uranium exposure because uranium accumulates in the proximal tubules and causes tubular damage, but the chemical nature of uranium in kidney, such as its chemical status in the toxic target site, is poorly understood. Micro‐X‐ray absorption fine‐structure (µXAFS) analysis was used to examine renal thin sections of rats exposed to uranyl acetate. The U L III ‐edge X‐ray absorption near‐edge structure spectra of bulk renal specimens obtained at various toxicological phases were similar to that of uranyl acetate: their edge position did not shift compared with that of uranyl acetate (17.175 keV) although the peak widths for some kidney specimens were slightly narrowed. µXAFS measurements of spots of concentrated uranium in the micro‐regions of the proximal tubules showed that the edge jump slightly shifted to lower energy. The results suggest that most uranium accumulated in kidney was uranium (VI) but a portion might have been biotransformed in rats exposed to uranyl acetate.